Application of medium-entropy ceramic as chiral recognition material, quartz crystal resonator and preparation method thereof, and quartz crystal microbalance sensor
By using a medium-entropy ceramic film as a chiral recognition layer on a quartz crystal resonator, the problem of failure of the chiral recognition layer in high-temperature environments in the existing technology is solved, and efficient enantiomers of serine and cysteine are achieved. identify, and improve material stability.
Patent Information
- Application Number
- CN202411368182.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
Smart Images

Figure BDA0005066831200000101 
Figure HDA0005066831210000011 
Figure HDA0005066831210000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and in particular to application of medium-entropy ceramics as chiral recognition materials, a quartz crystal resonator and a preparation method thereof, and a quartz crystal microbalance sensor. Background Art
[0002] Chirality is one of the basic properties of nature, and chiral molecules are widely present in nature and living organisms. In chemistry, molecular chirality refers to a molecule with the same chemical composition but with two or more structural forms. Chirality is asymmetry, just like the relationship between the left and right hands, which are mirror images of each other but cannot overlap; the two forms of chiral molecules are usually called enantiomers. Chirality plays a very important role and unique functions in various fields such as chemistry, biology, pharmacology and agriculture. Since enantiomers often have different biological activities, chiral recognition and separation play a vital role in the production and application of chiral molecules.
[0003] The identification of chiral molecules can be mainly divided into the following methods: chromatography, spectroscopy, mass spectrometry and chiral sensor method. Among them, the chiral sensor method is a method of detecting enantiomers by constructing a chiral detection surface and using electrochemical, optical or mass sensitive sensors. The chiral sensor method is widely used because of its high sensitivity, low detection limit and real-time monitoring of adsorption state. Chiral sensors use the changes in some physical and chemical properties of chiral recognition materials after interacting with enantiomers. These changes can be converted into information outputs such as optical signals and electrical signals according to certain rules, thereby identifying enantiomers. Common chiral sensors include optical sensors, mass sensors and electrochemical sensors. Quartz crystal microbalance (QCM) sensor is a type of mass sensor. Using the principle that the oscillation frequency change of the quartz crystal resonator is proportional to the mass change of the crystal surface, the mass change of the sensor surface in the nanogram (ng) level can be detected. Due to its simple structure, low cost, high resolution, high sensitivity, good specificity, and real-time online monitoring, it has become a key analytical method for realizing efficient identification of chiral molecules.
[0004] The QCM sensor is mainly composed of a quartz crystal resonator, an oscillator, a frequency counter, signal detection and data processing, a power supply, and other parts. Among them, the core of the QCM sensor is the quartz crystal resonator. The quartz crystal resonator is the receiver and converter of the sensor, and its main components are: a quartz crystal substrate, electrodes plated on both sides of the quartz crystal (generally inert metals such as gold, silver, nickel, chromium, platinum, etc.). The QCM chiral sensor itself does not have the ability to recognize chirality, and the realization of its chiral recognition function depends on the chiral recognition layer on the surface of the electrode. That is, in practical applications, in order to realize chiral recognition, a sensitive film with a specific selective recognition function is usually modified on the surface of the electrode as a chiral recognition layer.
[0005] For the QCM sensor based on the mass effect, in the thickness shear vibration mode, the material change on the surface of the quartz crystal causes the change of the crystal thickness, thereby causing the change of the crystal vibration frequency; in chiral recognition, different isomers have different frequency changes, thereby realizing chiral recognition. Specifically, the action principle of QCM on chiral compounds is based on the adsorption-desorption process of the analyte in the chiral recognition layer; the determination method is generally to place a quartz crystal with a chiral recognition layer in a detection cell, add the enantiomer sample to be measured, and the enantiomer and the chiral recognition layer undergo chiral recognition, and measure the change in its response frequency. Since the change in the QCM frequency at equilibrium is proportional to the adsorption amount of the enantiomer in the chiral recognition layer, the difference in the effect of the chiral recognition layer on the two isomers can be analyzed by comparing the change in the frequency of the two isomers at equilibrium, thereby identifying the two isomers.
[0006] Existing chiral recognition layer materials are mainly divided into two categories: 1. Metals; 2. Organic molecules; 3. Chiral nanostructured ceramics.
[0007] As for metals, researchers believe that metals are potential chiral materials for identifying and separating amino acid enantiomers due to the strong interaction between the substrate and the enantiomers. However, metals usually have high symmetry and are difficult to have chirality. Researchers have endowed their surfaces with chirality through techniques such as extended high-index direction cutting or chiral encoding, giving them high enantiomeric selectivity. However, due to the entropy gain effect, high surface energy, and low coordination number of atoms at the kink point, the surfaces of these defects often undergo reconstruction, causing the kink point to collapse and the step surface to merge, resulting in a decrease in the concentration of chiral surfaces. For example, in a real experimental environment, inorganic metal films lose their chirality within 30 minutes. In other words, in general, chiral metal surfaces have poor thermodynamic and kinetic stability due to high surface energy and low coordination number, and are prone to relaxation, causing the surface to lose chirality and fail.
[0008] For the organic molecular functional recognition layer, traditional chiral recognition materials mainly include amino acids and their derivatives, cyclodextrins, metal / covalent organic frameworks, molecular imprinting polymers, etc. However, due to its viscoelasticity, the traditional chiral recognition layer inevitably causes oscillation dissipation and low transfer efficiency, making the detection response of the electrode complicated and the stability poor. Moreover, the recognition effect of some chiral recognition materials is poor and they cannot efficiently recognize enantiomers. Summary of the invention
[0009] In view of this, the present invention provides an application of medium entropy ceramics as chiral recognition materials, a quartz crystal resonator and a preparation method, and a quartz crystal microbalance sensor, aiming to achieve efficient recognition of enantiomers and improve the stability of chiral recognition.
[0010] The present invention provides an application of a medium entropy ceramic as a chiral recognition material, wherein the medium entropy ceramic is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.
[0011] Preferably, x=0.33-0.34, y=0.33-0.34, z=0.33-0.34.
[0012] Preferably, the medium entropy ceramic is used for chiral recognition of serine enantiomers or cysteine enantiomers.
[0013] The present invention also provides a quartz crystal resonator, wherein the chiral recognition layer comprises a medium entropy ceramic film; the medium entropy ceramic in the medium entropy ceramic film is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.
[0014] Preferably, x=0.33-0.34, y=0.33-0.34, z=0.33-0.34.
[0015] Preferably, it comprises the following components:
[0016] Quartz crystal matrix;
[0017] An electrode sheet compounded on the surface of the quartz crystal substrate;
[0018] A Cr transition layer composited on the surface of the electrode sheet;
[0019] A medium entropy ceramic film is compounded on the surface of the Cr transition layer.
[0020] The present invention also provides a method for preparing the quartz crystal resonator described in the above technical solution, comprising: forming a medium-entropy ceramic film by magnetron sputtering.
[0021] Preferably, including:
[0022] A) magnetron sputtering is performed on a quartz crystal electrode sheet to form a Cr transition layer on the electrode surface;
[0023] The quartz crystal electrode sheet comprises: a quartz crystal substrate and an electrode sheet compounded on the surface of the quartz crystal substrate;
[0024] B) performing magnetron sputtering again to form a medium-entropy ceramic film on the Cr transition layer;
[0025] C) Annealing treatment.
[0026] Preferably, in step B), the magnetron sputtering process includes:
[0027] The magnetron sputtering system coating chamber was evacuated to 1×10 -5 ~9×10 -5 Pa, then introduce protective gas, adjust the pressure of the coating chamber to 3.0-4.0 Pa, ignite and glow, then adjust the pressure to 0.3-1.0 Pa, adjust the sputtering power to 60-100 W, sputter for 10-30 minutes, and form a medium entropy ceramic film;
[0028] In step C), the annealing treatment conditions are: temperature 300-500° C., time 2-3 h.
[0029] The present invention also provides a quartz crystal microbalance sensor, wherein the resonator is the quartz crystal resonator described in the above technical solution or the quartz crystal resonator prepared by the preparation method described in the above technical solution.
[0030] The present invention provides an application of a medium entropy ceramic as a chiral recognition material, wherein the medium entropy ceramic is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1. The present invention also provides a quartz crystal resonator, wherein the chiral recognition layer comprises a medium entropy ceramic film; the medium entropy ceramic in the medium entropy ceramic film is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1. The present invention is the first to use medium entropy ceramics (Cr x Mo y Ta z )Si2 is used as a chiral recognition material, which can effectively recognize serine enantiomers and cysteine enantiomers. The present invention provides a medium entropy ceramic (Cr x Mo y Ta z )Si2 quartz crystal microbalance sensor can effectively chirally identify enantiomers and improve the stability of chiral recognition materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0032] Figure 1 is a schematic diagram of the structure of the CrSi2 unit cell; wherein, Figure 1 a is the top view, Figure 1 b is the front view;
[0033] Figure 2 is a schematic diagram of the structure of the (CrMoTa)Si2(0001) surface; wherein, Figure 2 a and 2b are the top and side views of a random structure in the constructed surface, respectively;
[0034] Figure 3 Schematic diagram of the surface structure evolution process of the entropy ceramics in the present invention;
[0035] Figure 4 is the free energy diagram of the escape process of a single atom on the surface of the entropy ceramic of the present invention;
[0036] Figure 5 is a transition state energy barrier diagram of a single atom diffusion process of the entropy ceramic in the present invention;
[0037] Figure 6 Schematic diagram of the high-throughput computational process for the selective adsorption of serine isomers;
[0038] Figure 7 is the adsorption configuration diagram of serine isomers on a (CrMoTa)Si2 surface; wherein, Figure 7 a and 7b are the adsorption configuration diagrams of two isomers of serine, respectively;
[0039] Figure 8 is the adsorption energy distribution diagram of L- and D-serine on 810 (CrMoTa)Si2 surfaces; Figure 8 a is the adsorption energy distribution function diagram of L-serine in different local chemical environments, Figure 8 b is the adsorption energy distribution function diagram of D-serine in different local chemical environments;
[0040] Fig. 9 is the adsorption tendency diagram of amino acids on the medium entropy ceramic surface after considering competitive adsorption; Fig. 9 a is the principle diagram of competitive adsorption. Fig. 9 b is the adsorption energy distribution function after considering competitive adsorption and the relationship between coverage and adsorption energy;
[0041] Fig.10 Schematic diagram of the process for preparing medium-entropy ceramics on the surface of QCM electrodes;
[0042] Fig.11 This is the frequency change diagram of serine on the surface of QCM electrode modified with medium entropy ceramic. DETAILED DESCRIPTION
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0044] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0045] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0046] In this article, when referring to the units of a data range, if there is a unit after the right endpoint only, it means that the units of the left and right endpoints are the same. For example, 1×10 -5 ~9×10 -5 Pa represents the left endpoint "1×10 -5 " and the right endpoint "9×10 -5 The unit of " is Pa.
[0047] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0048] The present invention provides an application of a medium entropy ceramic as a chiral recognition material, wherein the medium entropy ceramic is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1. In the present invention, x+y+z=1, that is, the molar ratio of (Cr+Mo+Ta) to Si is controlled to be 1:2.
[0049] In the present invention, preferably, x=0.33-0.34, y=0.33-0.34, z=0.33-0.34. That is, the three metal elements Cr, Mo, and Ta are approximately in equal proportions. In the present invention, more preferably, x=1 / 3, y=1 / 3, and z=1 / 3.
[0050] In the present invention, the medium entropy ceramic is used for chiral recognition of serine enantiomers or cysteine enantiomers. Chiral recognition materials generally have specificity. After a large number of studies and analyses, the applicant found that the medium entropy ceramic has good chiral recognition ability for serine enantiomers and cysteine enantiomers, but has almost no recognition effect on enantiomers of alanine and the like.
[0051] In the present invention, preferably, the application is as a chiral recognition layer in a quartz crystal resonator, and more specifically, as a chiral recognition layer in a quartz crystal resonator in a quartz crystal microbalance (QCM) sensor.
[0052] The present invention also provides a quartz crystal resonator, wherein the chiral recognition layer comprises a medium entropy ceramic film; the medium entropy ceramic in the medium entropy ceramic film is (Cr x Mo y Ta z )Si2; wherein 0<x<1, 0<y<1, 0<z<1, and x+y+z=1. The quartz crystal resonator is the core component of the quartz crystal microbalance (QCM) sensor and is crucial for the quartz crystal microbalance (QCM) sensor to achieve chiral recognition.
[0053] In the present invention, preferably, x=0.33-0.34, y=0.33-0.34, z=0.33-0.34. That is, the three metal elements Cr, Mo, and Ta are approximately in equal proportions. In the present invention, more preferably, x=1 / 3, y=1 / 3, and z=1 / 3.
[0054] In the present invention, preferably, the quartz crystal resonator comprises the following components:
[0055] Quartz crystal matrix;
[0056] An electrode sheet compounded on the surface of the quartz crystal substrate;
[0057] A Cr transition layer composited on the surface of the electrode sheet;
[0058] A medium entropy ceramic film is compounded on the surface of the Cr transition layer.
[0059] In the present invention, the quartz crystal substrate is not particularly limited and can be any conventional quartz crystal substrate in quartz crystal resonators in the art.
[0060] In the present invention, the quartz crystal resonator further includes an electrode sheet compounded on the surface of the quartz crystal substrate, that is, the electrode sheet is compounded on the surface of the quartz crystal substrate; more specifically, it includes electrode sheets compounded on both surfaces of the quartz crystal substrate, that is, electrode sheets are compounded on both surfaces of the quartz crystal substrate (upper and lower surfaces, or front and back surfaces). In the present invention, the type of the electrode sheet is not particularly limited, and it can be any conventional electrode type in the art, generally an inert metal, such as gold, silver, nickel, chromium, platinum, etc.
[0061] In the present invention, the quartz crystal resonator further includes a Cr transition layer compounded on the surface of the electrode sheet, that is, a Cr metal transition layer is compounded on the surface of the electrode sheet. The upper and lower surfaces of the quartz crystal substrate are compounded with electrode sheets, and when the Cr transition layer is compounded on the surface of the electrode sheet, the Cr transition layer is compounded on one of the electrode sheets. In the present invention, the thickness of the Cr transition layer is preferably 5 to 20 nm, specifically 5 nm, 10 nm, 15 nm, 20 nm, and more preferably 10 nm.
[0062] In the present invention, the quartz crystal resonator further comprises a medium entropy ceramic film compounded on the surface of the Cr transition layer, that is, a medium entropy ceramic film is compounded on the surface of the Cr transition layer. In the present invention, the thickness of the medium entropy ceramic film is preferably 80 to 100 nm, specifically 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, and more preferably 90 nm. The medium entropy ceramic component in the medium entropy ceramic film is consistent with that described above, and will not be repeated here.
[0063] The present invention also provides a method for preparing the quartz crystal resonator described in the above technical solution, comprising: forming a medium-entropy ceramic film by magnetron sputtering.
[0064] In the present invention, preferably, the preparation method comprises the following steps:
[0065] A) magnetron sputtering is performed on a quartz crystal electrode sheet to form a Cr transition layer on the electrode surface;
[0066] The quartz crystal electrode sheet comprises: a quartz crystal substrate and an electrode sheet compounded on the surface of the quartz crystal substrate;
[0067] B) performing magnetron sputtering again to form a medium-entropy ceramic film on the Cr transition layer;
[0068] C) Annealing treatment.
[0069] [About Step A]:
[0070] In the present invention, there is no special restriction on the method of obtaining the quartz crystal electrode sheet. For example, the electrode slot of the existing quartz crystal microbalance (QCM) can be disassembled to take out the quartz crystal electrode sheet therein; or when the QCM is produced and assembled, after the quartz crystal matrix and the electrode sheet are assembled, other assembly processes are not performed temporarily and the quartz crystal electrode sheet is directly used. Among them, for the first acquisition method, after the quartz crystal electrode sheet is taken out, it is preferably pre-treated first. In the present invention, the pre-treatment preferably includes: washing and drying. Among them, the washing preferably includes: applying acid to the surface of the quartz crystal electrode sheet, standing, and then rinsing until no bubbles are generated, and then rinsing with water. Among them, the acid is preferably piranha acid. The application method can be dripping. The standing time is preferably 30s. The acid is applied to the surface of the electrode sheet and allowed to stand, and then rinsed after the organic matter on the surface is completely oxidized. The rinsing is preferably rinsed with anhydrous ethanol; after there are no bubbles, rinse with water to remove the residual anhydrous ethanol. The water is preferably deionized water. After the above washing, it is dried. The drying method is not particularly limited and can be carried out in accordance with conventional drying methods in the art, such as drying in a constant temperature drying oven. After the above washing and drying treatments, a clean quartz crystal electrode sheet is obtained.
[0071] In the present invention, before magnetron sputtering the quartz crystal electrode sheet, it is preferred to perform masking treatment first, that is, to cover the quartz area to ensure that only the electrode is exposed outside, thereby ensuring that during subsequent magnetron sputtering, the Cr transition layer is sputtered only on the electrode surface.
[0072] In the present invention, when preparing the Cr transition layer by magnetron sputtering, a Cr target is preferably used as a sputtering target. In the present invention, when preparing the Cr transition layer by magnetron sputtering, the sputtering mode used is preferably a DC mode. In the present invention, the process of preparing the Cr transition layer by magnetron sputtering preferably includes: evacuating the coating chamber of the magnetron sputtering system to 1×10 -5 ~9×10 -5 Pa, then introduce protective gas, adjust the pressure of the coating chamber to 3.0-4.0 Pa, ignite and glow, then adjust the pressure to 0.4-1.0 Pa, adjust the sputtering power to 30-50 W, sputter for 5-20 seconds, and form a Cr transition layer. -5 ~9×10 -5 Pa, specifically 1×10 -5 Pa, 2×10 -5 Pa, 3×10 -5 Pa, 4×10 -5 Pa, 5×10 -5 Pa, 6×10 -5 Pa, 7×10 -5 Pa, 8×10 -5Pa, 9×10 -5 Pa. The protective gas is preferably argon. The coating chamber pressure is adjusted to 3.0-4.0 Pa, specifically 3.0 Pa, 3.1 Pa, 3.2 Pa, 3.3 Pa, 3.4 Pa, 3.5 Pa, 3.6 Pa, 3.7 Pa, 3.8 Pa, 3.9 Pa, 4.0 Pa. After ignition, the pressure is adjusted to 0.4-1.0 Pa, specifically 0.4 Pa, 0.5 Pa, 0.6 Pa, 0.7 Pa, 0.8 Pa, 0.9 Pa, 1.0 Pa. The sputtering power is specifically 30 W, 35 W, 40 W, 45 W, 50 W. The sputtering time is specifically 5 s, 10 s, 15 s, 20 s. In the present invention, the thickness of the Cr transition layer is preferably 5-20 nm, specifically 5 nm, 10 nm, 15 nm, 20 nm, and more preferably 10 nm.
[0073] [About step B]:
[0074] In the present invention, after the Cr transition layer is formed by magnetron sputtering in step A, magnetron sputtering is performed again on the basis of the Cr transition layer to form a medium-entropy ceramic film on the surface thereof.
[0075] In the present invention, when preparing the medium entropy ceramic film by magnetron sputtering, a multiphase alloy target of Cr, Mo, Ta and Si is used. In the multiphase alloy target, the molar ratio of (Cr+Mo+Ta) to Si is 1:2. In the multiphase alloy target, the three metal elements Cr, Mo and Ta are approximately in equal proportions. The multiphase alloy target can be customized by Hefei Kejing Materials Technology Co., Ltd.
[0076] In the present invention, when preparing the medium entropy ceramic film by magnetron sputtering, the sputtering mode used is preferably a radio frequency mode. In the present invention, the process of preparing the medium entropy ceramic film by magnetron sputtering preferably includes: evacuating the coating chamber of the magnetron sputtering system to 1×10 -5 ~9×10 -5 Pa, then introduce protective gas, adjust the pressure of the coating chamber to 3.0-4.0 Pa, ignite and glow, then adjust the pressure to 0.3-1.0 Pa, adjust the sputtering power to 60-100 W, sputter for 10-30 min, and form a medium entropy ceramic film. -5 ~9×10 -5 Pa, specifically 1×10 -5 Pa, 2×10 -5 Pa, 3×10 -5 Pa, 4×10 -5 Pa, 5×10 -5 Pa, 6×10 -5 Pa, 7×10 -5 Pa, 8×10-5 Pa, 9×10 -5 Pa. The protective gas is argon. The coating chamber pressure is adjusted to 3.0-4.0Pa, specifically 3.0Pa, 3.1Pa, 3.2Pa, 3.3Pa, 3.4Pa, 3.5Pa, 3.6Pa, 3.7Pa, 3.8Pa, 3.9Pa, 4.0Pa. After ignition, the pressure is adjusted to 0.3-1.0Pa, specifically 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa, 1.0Pa. The sputtering power can be 60W, 70W, 80W, 90W, 100W. The sputtering time can be 10min, 15min, 20min, 25min, 30min. By the above-mentioned magnetron sputtering, a medium-entropy ceramic film is formed on the Cr transition layer. The medium-entropy ceramic is consistent with that described in the previous technical solution and will not be repeated here. In the present invention, the thickness of the medium-entropy ceramic film is preferably 80-100 nm, specifically 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, and more preferably 90 nm.
[0077] [About Step C]:
[0078] In the present invention, after the magnetron sputtering in step B) is completed, the quartz crystal electrode sheet is removed, the mask is torn off, and annealing is performed. In the present invention, the annealing is preferably performed in a protective atmosphere. Among them, the protective gas providing the protective atmosphere is preferably argon. In the present invention, the temperature of the annealing is preferably 300-500°C, specifically 300°C, 350°C, 400°C, 450°C, 500°C. The annealing time is preferably 2-3h, specifically 2.0h, 2.5h, 3.0h. After the above annealing treatment, the atoms can be fully diffused, the defects can be reduced, the adhesion strength can be improved, and the medium entropy ceramic film can be firmly loaded on the surface of the QCM electrode, thereby obtaining a quartz crystal resonator with a medium entropy ceramic film chiral recognition layer.
[0079] The present invention also provides a quartz crystal microbalance sensor, wherein the resonator is the quartz crystal resonator described in the above technical solution or the quartz crystal resonator prepared by the preparation method described in the above technical solution.
[0080] Previous studies and applications have all used organic molecules as chiral recognition materials. This invention proposes for the first time the use of chiral inorganic solid materials (medium entropy ceramics (Cr x Mo y Ta z )Si2) as a chiral recognition material, which can effectively recognize serine enantiomers and cysteine enantiomers. The present invention provides a medium entropy ceramic (Cr x Moy Ta z )Si2 quartz crystal microbalance sensor can effectively chirally identify enantiomers and improve the stability of chiral recognition materials.
[0081] The applicant is interested in medium entropy ceramics (Cr x Mo y Ta z ) A lot of exploration and analysis have been conducted on the feasibility of Si2 as a chiral recognition material. The analysis methods include:
[0082] (1) Based on CrSi2-type medium-entropy ceramics with a space group of P6222, 50 random (Cr) x Mo y Ta z ) The structure of Si2 medium-entropy ceramics and the lattice constant of the medium-entropy ceramics were determined;
[0083] (2) Through first-principles high-throughput calculation, the above 50 random (Cr x Mo y Ta z ) The stable structure and energy of Si2 medium-entropy ceramics, the balance between entropy increase and enthalpy cost were analyzed, and it was proved that the medium-entropy ceramics have good forming ability;
[0084] (3) Construct 10 random 4-layer (Cr x Mo y Ta z ) Si2 medium entropy ceramic slab model, calculate the energy and potential barriers of the escape, diffusion and aggregation process of metal and non-metal atoms on the surface of the model;
[0085] (4) High-throughput construction of 4 layers (Cr x Mo y Ta z ) Si2 medium entropy ceramic slab model, calculate the adsorption structure and adsorption energy of serine enantiomers on its surface;
[0086] (5) Considering the competitive relationship between the enantiomers when they are mixed, the 810 (Cr x Mo y Ta z )The adsorption tendency of Si2 medium-entropy ceramic slab model for amino acid isomers was calculated, and the adsorption selectivity of medium-entropy ceramic for serine was statistically analyzed.
[0087] In the present invention, the above step (1) specifically includes: importing a CrSi2 ceramic crystal structure with a P6222 space group from the Materials Project database, expanding the cell in the x and y directions to obtain a (2×2×1) supercell, and exporting the CrSi2 crystal after the expansion; calling Python's random seed module to replace its metal sites with Cr, Mo, and Ta in equal atomic molar ratios to obtain 50 random medium-entropy ceramic structure block materials, optimizing their structures using VASP software, and obtaining lattice constants under stable structures.
[0088] In the present invention, in the above step (2), the method for predicting the surface thermal stability and structural evolution ability of the medium entropy ceramic is as follows:
[0089] The structure and energy of the entropy ceramics in the 50 different element arrangements constructed above were calculated, and the total energy distribution function was obtained, and the energy distribution spectrum (H i ) to obtain the EFA value:
[0090]
[0091] Where n is the number of sampling structures, g i is the degeneracy of energy, H mix is the mixing enthalpy. The formation ability of the medium-entropy ceramic is determined according to the EFA value. Ten different medium-entropy ceramic slab models are constructed to calculate the energy required for the surface Si and metal atoms to form adsorbed atoms, as well as the transition state barrier when the adsorbed atoms diffuse on the surface, to determine their structural evolution ability.
[0092] In the actual analysis operation, the (CrMoTa)Si2(0001) surface is constructed, and the free energy change and energy barrier (such as Figure 3 Calculate the formation energy of the most unstable atom escaping from the surface of the medium entropy ceramic to form an adsorbed atom (as shown in Figure 4 The NEB transition state energy barrier algorithm is used to calculate the energy barrier of the most unstable atom escape process on the surface of medium entropy ceramics (as shown in Figure 5 As shown), the thermodynamic stability of medium-entropy ceramics is obtained.
[0093] In the present invention, in the above steps (4)-(5), the method for constructing the adsorption structure and energy of serine isomers on the entropy ceramic slab model of 810 different element arrangements is as follows:
[0094] Using the random seed method in Python, a medium-entropy ceramic film with 810 different element arrangements was constructed in a high-throughput manner. According to the pre-adsorption structure of serine isomers on the CrSi2 ceramic surface, the adsorption structure of serine isomers on the surface of chiral ceramic films was constructed. The constructed adsorption structure was optimized using high-throughput calculations to obtain the adsorption energy.
[0095] In actual analysis, batch construction of the adsorption interface of serine isomers on the medium entropy ceramic surface (such as Figure 6 The local most stable adsorption structure of serine on the medium entropy ceramic surface was obtained by DFT calculation (as shown in Figure 7 The adsorption structures and adsorption energies of serine isomers on 810 different medium entropy ceramic surfaces were statistically calculated by high-throughput calculation, and the adsorption energy distribution curve was obtained (as shown in Figure 8 Considering the competition problem of serine isomers during co-adsorption, the adsorption tendency of each mesentropy ceramic unit cell to serine isomers was compared, and the adsorption energy distribution curve and adsorption selectivity during co-adsorption were obtained (as shown in Fig. Fig. 9 shown).
[0096] In actual analysis, the method is as follows:
[0097] S1. Use the Materials Projects database to export CrSi2 crystals with C40 crystal structure (such as Figure 1 The CrSi2 crystal after cell expansion is derived.
[0098] S2. Using the random seed method in Python, the metal sites in the CrSi2 crystal obtained in (1) were randomly replaced with Cr, Mo, and Ta in equal atomic ratios to obtain random medium-entropy ceramic structures (such as Figure 2 The obtained medium-entropy ceramic structure was optimized by DFT calculation to obtain the average lattice constant of the medium-entropy ceramic.
[0099] S3. Construct the (CrMoTa)Si2(0001) surface and consider the free energy change and energy barrier of the surface atom escape process (such as Figure 3 Calculate the formation energy of the most unstable atom escaping from the surface of the medium entropy ceramic to form an adsorbed atom (as shown in Figure 4 shown).
[0100] S4. The NEB transition state energy barrier algorithm is used to calculate the energy barrier of the most unstable atom escape process on the surface of medium entropy ceramics (such as Figure 5 As shown), the thermodynamic stability of medium-entropy ceramics is obtained.
[0101] S5. Batch construction of adsorption interface of serine isomers on medium entropy ceramic surface (e.g. Figure 6 The local most stable adsorption structure of serine on the medium entropy ceramic surface was obtained by DFT calculation (as shown in Figure 7 shown).
[0102] S6. The adsorption structures and adsorption energies of serine isomers on 810 different medium-entropy ceramic surfaces were calculated by statistical high-throughput calculations, and the adsorption energy distribution curves were obtained (e.g. Figure 8 shown).
[0103] S7. Considering the competition problem of serine isomers during co-adsorption, the adsorption tendency of each mesentropy ceramic unit cell to serine isomers was compared to obtain the adsorption energy distribution curve and adsorption selectivity during co-adsorption (such as Fig. 9 shown).
[0104] Aiming at the thermal stability of intermediate entropy ceramics, the surface structure evolution of intermediate entropy ceramics was calculated by first-principles density functional theory method. Intermediate entropy ceramics belong to the CrSi2 type crystal structure, such as Figure 1 Its surface structure is as shown in Figure 2 The structural evolution process of the medium entropy ceramic surface includes: surface atomic escape, diffusion and reaggregation, such as Figure 3 As shown. The escape of surface atoms is the key to determining whether the structural evolution process can be started. By calculating the energy required for the most unstable atom on the surface to escape, it is found that the structural evolution of medium-entropy ceramics is more difficult to start than that of conventional chiral metal surfaces. Figure 4 As shown. Through the transition state energy barrier of the escaping atomic diffusion process, it is found that the diffusion energy barrier of the atoms on the medium entropy ceramic surface is twice that of the chiral metal surface, indicating that the probability of the diffusion process is two orders of magnitude smaller than that of the atoms on the chiral metal surface, as shown in Figure 5 As shown. Therefore, the above results can prove that the thermal stability of the medium-entropy ceramic is higher than that of the chiral metal surface. In order to further verify whether the medium-entropy ceramic can be used as a chiral recognition material, we built a high-throughput computational flow, such as Figure 6 shown. Figure 7 The adsorption structure of L-serine and D-serine in a local chemical environment is shown. In order to avoid the influence of random distribution of metal atoms in medium-entropy ceramics on chiral selectivity, we calculated the adsorption structure and adsorption energy of L-serine and D-serine in 810 different local chemical environments with high throughput. By statistically analyzing them, we obtained the adsorption energy distribution function of L-serine and D-serine on the surface of medium-entropy ceramics, such as Figure 8 By comparing the adsorption tendency of L-serine and D-serine under different local chemical environments, the adsorption energy distribution function during competitive adsorption and the relationship between surface coverage and adsorption energy were obtained. It was found that after considering competitive adsorption, 71% of the sites were more inclined to adsorb L-serine, while 29% of the sites were more inclined to adsorb D-serine, as shown in Figure 2. Fig. 9 shown.
[0105] In addition, a model was constructed according to the above analysis method to study the adsorption behavior of cysteine isomers, and the adsorption selectivity of cysteine isomers on the surface of the above-mentioned medium-entropy ceramic was obtained. It was proved that the medium-entropy ceramic can also effectively identify cysteine isomers.
[0106] Mesentropy ceramics are a new type of ceramic material. Unlike traditional ceramics, which are usually composed of one or a few components, mesentropy ceramics are composed of multiple components mixed in nearly equal proportions. The entropy of mesentropy ceramics refers to the distribution disorder or diversity of the components in the material. The design of chiral recognition materials based on mesentropy ceramics is a relatively new and complex field, because mesentropy ceramics itself, as a multi-component alloy ceramic, focuses on the diversity and disorder of components, and chiral recognition requires the material to have a specific chiral microenvironment or structure. Therefore, the use of mesentropy ceramics as chiral recognition materials faces great challenges.
[0107] Due to the disorder or diversity of the distribution of medium entropy ceramic components, the present invention constructs (Cr x Mo y Ta z )Si2 medium-entropy ceramic structure and high-throughput calculations have proved that the above-mentioned medium-entropy ceramic materials can be used as chiral recognition materials and have a good recognition effect on amino acid isomers.
[0108] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0109] Example 1
[0110] 1. Preparation of quartz crystal resonator
[0111] Preparation process Fig.10 As shown, the specific process is as follows:
[0112] The QCM electrode tank was disassembled, and the quartz crystal electrode was taken out. 1 mL of piranha acid solution was dropped onto the quartz crystal electrode. After it was left to stand for 30 seconds, the organic matter on its surface was completely oxidized, and then it was rinsed with anhydrous ethanol until no bubbles were generated. Next, deionized water was used to rinse the electrode surface to remove the residual alcohol, and the electrode was placed in a constant temperature drying oven for drying to obtain a clean quartz crystal electrode.
[0113] The quartz area of the quartz crystal electrode sheet was masked with weighing paper to ensure that only the electrode surface was exposed, and it was adhered to the center of the substrate of the magnetron sputtering system, and magnetron sputtering was performed using it as the matrix. The DC mode was first used to sputter the Cr transition layer, as follows: Cr target was used as the target material, and the coating chamber of the magnetron sputtering system was evacuated to 1×10 -5Pa, then turn on argon, adjust the gas pressure in the coating chamber to 3.0 Pa, ignite and glow, then adjust the gas pressure to 0.4 Pa, adjust the sputtering power to 40 W, sputter for 10 seconds, and form a Cr transition layer with a thickness of about 10 nm.
[0114] The medium entropy ceramic film was sputtered on the basis of the above Cr transition layer, specifically as follows: using the radio frequency mode, a multiphase alloy of Cr, Mo, Ta and Si was used as the target material (wherein the molar ratio of Cr+Mo+Ta to Si was 1:2, and Cr, Mo and Ta were in equal proportions); the coating chamber of the magnetron sputtering system was evacuated to 1×10 -5 Pa, then turn on argon, adjust the pressure in the coating chamber to 3.0Pa, ignite and glow, then adjust the pressure to 0.4Pa, adjust the sputtering power to 70W, sputter for 10min, and form (Cr 1 / 3 Mo 1 / 3 Ta 1 / 3 )Si2 medium-entropy ceramic thin film.
[0115] After sputtering, the quartz crystal electrode sheet was taken out, the mask was torn off, and it was placed in a tube furnace in an argon atmosphere at 500°C for annealing for 2 hours to obtain a quartz crystal resonator with a medium-entropy ceramic thin film chiral recognition layer.
[0116] 2. Testing
[0117] The quartz crystal resonator prepared in Example 1 was placed in 400 mL of water, and then 20 μL of a 0.3 M serine isomer solution (i.e., a mixed solution of L-serine and D-serine) was added dropwise, and the above-mentioned addition operation was repeated (i.e., after the first addition of 20 μL of serine isomer solution, the solution was allowed to stand for 300 s, and 20 μL of serine isomer solution was added dropwise for the second time, and so on), and the adsorption amount of serine was monitored in real time. It was found that after 5 additions, the adsorption amount signal of L-serine was 144 Hz, while the adsorption amount signal of D-serine was only 102 Hz, and the adsorption amount of L-serine was 1.41 times that of D-serine, that is, the adsorption of L-serine by the above-mentioned medium entropy ceramic was significantly stronger than that of D-serine, as shown in FIG. Fig.11 As shown, it is proved that the above-mentioned medium-entropy ceramics can be used as chiral recognition materials to efficiently recognize serine isomers.
[0118] In addition, high-index chiral metal surfaces will lose chirality during the experiment, thereby losing the recognition effect and having poor stability. The chiral recognition material of the present invention was annealed at 500°C before the adsorption selectivity experiment and was still able to recognize serine, showing excellent stability.
[0119] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. Application of a medium entropy ceramic as a chiral recognition material, wherein: The medium entropy ceramic is (Cr x Mo y Ta z )Si2; Among them, 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.
2. The use according to claim 1, characterized in that: x=0.33~0.34, y=0.33~0.34, z=0.33~0.
34.
3. The use according to claim 1, characterized in that: The medium entropy ceramic is used for chiral recognition of serine enantiomers or cysteine enantiomers.
4. A quartz crystal resonator, characterized in that: The chiral recognition layer comprises a medium entropy ceramic film; the medium entropy ceramic in the medium entropy ceramic film is (Cr x Mo y Ta z )Si2; Among them, 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.
5. The quartz crystal resonator according to claim 1, characterized in that: x=0.33~0.34, y=0.33~0.34, z=0.33~0.
34.
6. The quartz crystal resonator according to claim 1, characterized in that: It includes the following components: Quartz crystal matrix; An electrode sheet compounded on the surface of the quartz crystal substrate; A Cr transition layer composited on the surface of the electrode sheet; A medium entropy ceramic film is compounded on the surface of the Cr transition layer.
7. A method for preparing a quartz crystal resonator according to any one of claims 4 to 6, characterized in that: include: Medium-entropy ceramic thin films were formed by magnetron sputtering.
8. The preparation method according to claim 7, characterized in that: include: A) magnetron sputtering is performed on a quartz crystal electrode sheet to form a Cr transition layer on the electrode surface; The quartz crystal electrode sheet comprises: a quartz crystal substrate and an electrode sheet compounded on the surface of the quartz crystal substrate; B) performing magnetron sputtering again to form a medium-entropy ceramic film on the Cr transition layer; C) Annealing treatment.
9. The preparation method according to claim 8, characterized in that: In step B), the magnetron sputtering process includes: The magnetron sputtering system coating chamber was evacuated to 1×10 -5 ~9×10 -5 Pa, then introduce protective gas, adjust the pressure of the coating chamber to 3.0-4.0 Pa, ignite and glow, then adjust the pressure to 0.3-1.0 Pa, adjust the sputtering power to 60-100 W, sputter for 10-30 minutes, and form a medium entropy ceramic film; In step C), the annealing treatment conditions are: temperature 300-500° C., time 2-3 h.
10. A quartz crystal microbalance sensor, characterized in that: The resonator is a quartz crystal resonator according to any one of claims 4 to 6 or a quartz crystal resonator prepared by the preparation method according to any one of claims 7 to 9.